Indian Muslims in freedom struggle - Chopra, Pran Nath. (New Delhi : Criterion Publications, 1988)
Chiefly political biographies of renowned nationalist Muslim leaders.
Includes index.
Bibliography: p. [250]-254.
Keywords: Muslims -- India -- Biography